Molecular characterization of the gene encoding SHV-3 beta-lactamase responsible for transferable cefotaxime resistance in clinical isolates of Klebsiella pneumoniae. - Nicolas, M H (1989)
In Klebsiella pneumoniae 86-4, cefotaxime resistance was due to a transferable broad-spectrum beta-lactamase, SHV-3. The plasmid-borne gene encoding SHV-3 has been cloned, and the primary structure of the enzyme was deduced from its nucleotide sequence. SHV-3 differs from SHV-1 in two positions. The extended substrate profile of SHV-3 probably results from the substitution of Ser-213 for Gly, as in SHV-2, whereas replacement of Arg-180 by Leu resulted in a decrease in the pI from 7.6 to 7.0. The blashv-3 gene is highly homologous (92% DNA sequence identity) with the chromosomal gene coding for LEN-1 beta-lactamase of K. pneumoniae, suggesting that the origin of the SHV-encoding genes now present on many plasmids may be chromosomal.